2015
DOI: 10.5751/ace-00734-100112
|View full text |Cite
|
Sign up to set email alerts
|

Piping Plover response to coastal storms occurring during the nonbreeding season

Abstract: However, to our knowledge, no test of this pattern has been conducted over a regional scale. We hypothesized that Piping Plover abundance would increase after large coastal storms occurring during the nonbreeding season. However, we expected a delay in the colonization of newly created habitat owing to low-density populations, combined with high site fidelity of adults and high variability in survival rate of subadults. We tested this hypothesis using a 27-year (1986-2012) data set of Piping Plover abundance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…As also observed by Bourque et al [88], we found that the relationship between the storm-induced increase in habitat and piping plover population size was less clear. Population sizes, measured as the number of breeding pairs, remained steady or declined from the pre-Sandy (spring 2012) through the ca.…”
Section: Resultssupporting
confidence: 73%
“…As also observed by Bourque et al [88], we found that the relationship between the storm-induced increase in habitat and piping plover population size was less clear. Population sizes, measured as the number of breeding pairs, remained steady or declined from the pre-Sandy (spring 2012) through the ca.…”
Section: Resultssupporting
confidence: 73%
“…A study in eastern Canada, near the northern end of the Piping Plover's Atlantic Coast range, found that the number of fledglings increased following winter storms similar to Hurricane Isabel and the nor'easters reported here (Bourque et al 2015). However, Bourque et al (2015) did not find a strong relationship with pair counts, suggesting that the amount of habitat created following storms was too little to change the amount of available nesting habitat significantly given the current population, but did allow for more foraging habitat for prefledged chicks. Alternatively, other factors could be affecting this population's growth rate such as factors outside of the breeding season.…”
Section: Discussionmentioning
confidence: 49%